Kontribusi Usaha Sarang Burung Walet Dalam Peningkatan Pendapatan Ekonomi Masyarakat Menurut Perspektif Ekonomi Syariah - Mawardi Muhammad Saleh; Wahyu Puji Ambarraras; Indra Hadi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
This research is motivated by increasing people's economic income with the establishment of a swallow's nest business; this research will focus on the contribution of the swallow's nest business to growing people's financial income with the aim of knowing the form of the actual assistance of the swallow's nest business in improving the economy of the people of Sumber Sari Village. Jaya. The population used in this study were all owners of swallow's nest businesses in Sumber Sari Jaya Village, Teluk Belengkong District, Indragiri Hilir Regency, totaling ten people. In comparison, the sample in this study amounted to 9 people using the Purposive Sampling method. The research method used is descriptive qualitative using primary and secondary data sources. In contrast, the primary data sources are obtained directly from the owner of the swallow's nest business. In contrast, the secondary data sources are taken from documents or institutional literacy related to the research conducted. The results of the study that have been carried out show that the swallow's nest business has a reasonably high contribution to increasing people's economic income; this is evidenced by the 55.5% increase in the owner of the swallow's nest business from 2013 to 2019, harvest yields have also increased. Every harvest. Keywords: Contribution, Effort, Improvement, Economy